Information technologies in environmental engineering - Gómez, Jorge Marx (Management of environmental quality, 2004)
A soil information system was developed to manage soil survey data and to ensure that soil information is readily available to support land use planning and development. The Soil Information System combined spatial information management of a Geographical Information System (GIS) with the textural information management of a relational database management system. The GIS is capable of manipulating and displaying area and point data with the logical framework of a database to store data for interpretation. The main objective of this paper was to demonstrate one of the approaches to utilize and.